1969
DOI: 10.1029/ja074i026p06352
|View full text |Cite
|
Sign up to set email alerts
|

Nonducted mode of VLF propagation between conjugate hemispheres; Observations on OGO's 2 and 4 of the ‘walking-trace’ whistler and of Doppler shifts in fixed frequency transmissions

Abstract: Evidence for nonducted VLF propagation between conjugate hemispheres has been found in records from the broadband VLF receivers aboard the polar satellites OGO 2 (419–1521 km) and OGO 4 (412–908 km). The nonducted signals described here are received in the ionosphere between 47° and 56° invariant latitude. They have never been observed on the ground and include natural whistlers and fixed‐frequency signals (10.2–12.5 kHz) from the U.S. Navy Omega transmitters. In a time‐frequency spectrogram, these nonducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 9 publications
(1 reference statement)
2
28
0
Order By: Relevance
“…The diagnostic potential of the LHR in terms of ion composition or effective mass m eff has been demonstrated in passive studies of wave activity observed aboard low altitude polar orbiting satellites [e.g., Barrington et al , 1965; Brice and Smith , 1965] and now once again becomes evident as we investigate active probing at altitudes below ∼5000 km with IMAGE. At much higher altitudes, the phenomenon of MR reflection has in the past received considerable attention, but mostly as an aid in modeling the propagation of various VLF waves such as non ducted lightning whistlers [e.g., Edgar , 1976; Walter and Angerami , 1969; Bortnik et al , 2003] and emissions such as chorus [e.g., Bortnik et al , 2008] and hiss [e.g., Sonwalkar and Inan , 1989; Abel and Thorne , 1998]. Now, with the prospect of remotely sensing the distribution of f lh along B 0 , there is the prospect of using radio sounding at frequencies lower than the 6 kHz limit of the RPI programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic potential of the LHR in terms of ion composition or effective mass m eff has been demonstrated in passive studies of wave activity observed aboard low altitude polar orbiting satellites [e.g., Barrington et al , 1965; Brice and Smith , 1965] and now once again becomes evident as we investigate active probing at altitudes below ∼5000 km with IMAGE. At much higher altitudes, the phenomenon of MR reflection has in the past received considerable attention, but mostly as an aid in modeling the propagation of various VLF waves such as non ducted lightning whistlers [e.g., Edgar , 1976; Walter and Angerami , 1969; Bortnik et al , 2003] and emissions such as chorus [e.g., Bortnik et al , 2008] and hiss [e.g., Sonwalkar and Inan , 1989; Abel and Thorne , 1998]. Now, with the prospect of remotely sensing the distribution of f lh along B 0 , there is the prospect of using radio sounding at frequencies lower than the 6 kHz limit of the RPI programs.…”
Section: Discussionmentioning
confidence: 99%
“…These sounding operations have allowed us to observe the results of WM sounding in an altitude range not previously explored and at frequencies lower than those previously employed. In making preliminary assessments of the new data, we are able to draw upon existing knowledge of several important whistler mode propagation phenomena, notably (1) non‐ducted propagation, wherein wave‐normal directions are not constrained to remain within a small cone of angles around the direction of the geomagnetic field but are strongly affected by large‐scale spatial variations of the plasma parameters [e.g., Walter and Angerami , 1969; James , 1972; Cerisier , 1973; Sonwalkar et al , 1984], (2) the phenomenon of “magnetospheric reflection” (MR), in which the raypath of a wave propagating at large wave‐normal angle is reversed near a point where the refractive index surface undergoes an important change in topology and size (e.g., Kimura [1966], Smith and Angerami [1968], who introduced the term “magnetospheric reflection,” Edgar [1976], and Shklyar et al [2010]), (3) spreading of wave‐normals (and hence time delays) due to encounters with geomagnetic field aligned density irregularities (FAIs) of transverse scale sizes varying from 10 m to 100 km [e.g., James , 1972; Sonwalkar et al , 1984, 2004a], and (4) partial or complete reflection of downcoming waves at the sharp lower ionospheric boundary [e.g., Helliwell , 1965; Brittain et al , 1983; Sonwalkar et al , 2004a].…”
Section: Introductionmentioning
confidence: 99%
“…One of the first reports concerned observations from the OGO-4 spacecraft of VLF transmitter signals propagating from the northern hemisphere through the plasmasphere to the spacecraft in the southern hemisphere [Walter and Angerami, 1969]. The Doppler shifts observed on OGO-4 were a few hundred Hz.…”
Section: Discussionmentioning
confidence: 99%
“…tennas have been measured and the following results found: ( 1 ) the polarization of whistlers which penetrate the ionosphere close to the observing station is righthanded over a wide frequency range; and (2) some whistlers are found to have propagated over a distance of %1500 km. These whistlers exhibit a right-handed polarization at some frequencies and a left-handed polarization at other frequencies.…”
mentioning
confidence: 99%